Molecular Detection of Quinolone Resistance Mechanisms in Pseudomonas aeruginosa Isolates Recovered from Different Clinical Specimens in Babylon Province - Selman Mohammed Selman; Uday H. K. Al-Janabi; Faliha Habeeb Hussein; Hadi Fadhil Abed Almuhsin Alyasari (Medical Journal of Babylon, 2025)
Background: Pseudomonas aeruginosa is a common Gram-negative, rod-shaped, aerobic-facultatively anaerobic bacteria that can affect both animals and plants even people. It is a multidrug-resistant pathogen with significant medical significance. Objectives: The aim of the article is to detect the effect of genes DNA gyrA and topoisomerase IV ParC genes in resistance P. aeruginosa isolates recovered from different clinical specimens. Materials and Methods: The bacterial isolates were obtained from patients who had been admitted to Al-Hilla Teaching Hospital in Babylon, Iraq, with wounds, burns, urine, and blood. The disc diffusion method was used to determine the susceptibility of P. aeruginosa strains to levofloxacin, ciprofloxacin, and pefloxacin, as well as nitrofurantoin. DNA was extracted from bacteria and 16S rRNA oligonucleotide primers were used in training on traditional PCR thermocycler to identify antibiotic resistance. Results: Isolates were presented as the highest resistance to quinolones antibiotics: ciprofloxacin (80%), pefloxacin, nitrofurantoin (90%), and levofloxacin (40%). Molecular results by conventional PCR thermocyclers revealed that 17 (85%) out of 20 isolates carrying 16S rRNA; 16 (80%) isolates out of 20 P. aeruginosa had positive DNA gyrA and topoisomerase IV parC10 (50%) were positive. Conclusion: MDR P. aeruginosa isolates are predominant in burn specimens and most isolates carry the 16S rRNA gene and consider markers for the identification of this bacterium, all isolates have one or more genes responsible for quinolone resistance at different rates (DNA gyrA, topoisomerase IV ParC).